KERANGKA KERJA MANAJEMEN HUMAS DALAM LEMBAGA PENDIDIKAN - Jailani, Jailani (JURNAL AL-TANZIM, 2018)
Educational institutions are grown by initiative, one of which is certainly inseparable in so much the contribution of the existence of a mature planning with the preparation of a strategy / concept of management framework to create a quality educational institution. This journal describes a public relations management framework within educational institutions ranging from Planning, Organizing, Actuating, and Controlling. Public affairs and lobbying are high status and strategically important strategic public relations. It is a field of public relations practice that produces high levels both scientifically and publicly concerning the role it perceives in supporting the company's strengths and impacts related to the functional legitimacy of democratic institutions. For this paper content analysis is done from academic journals to provide insight into how public affairs and lobbying have been theorized and researched within it public relations scholarship and to ascertain what level of wider public concern has been addressed. The findings include empirical confirmation of a low level of research activity in public affairs; that rhetorical stakeholders and theories are the most widely used theories, but far from the dominant paradigm